DETERMINAN SOSIAL LINGKUNGAN KERJA DAN EPIDEMIOLOGI BURNOUT: TINJAUAN LITERATUR DAMPAK WORK-LIFE BALANCE DAN DUKUNGAN ORGANISASI TERHADAP KINERJA BIDAN PUSKESMAS DI LOMBOK TENGAH NTB - Baiq Reni Pratiwi; Yuly Peristiowati (Bajang Institute, 2026)
Background: Midwives at Community Health Centers (Puskesmas) are the spearhead of maternal and child health services, yet they are vulnerable to burnout due to high workloads. In Central Lombok, West Nusa Tenggara (WNT), work environment dynamics and lack of organizational support often trigger burnout phenomena. Objective: This study aims to analyze the social determinants of the work environment, specifically the impact of work-life balance (WLB) and organizational support on the epidemiology of burnout and midwife performance. Methods: This study employed a Systematic Literature Review (SLR) method. Literature search was conducted through Scopus, Google Scholar, and Portal Garuda databases within the 2016-2026 timeframe. Ten relevant articles were selected based on inclusion and exclusion criteria for synthesis. Results: Findings indicate that burnout is significantly negatively correlated with midwife performance. Conversely, strong work-life balance and organizational support act as protective factors that mitigate job stress and enhance service productivity. A supportive work environment in Puskesmas is proven to increase midwives' resilience in facing job demands in rural areas. Conclusion: Improving midwife performance in Central Lombok requires a managerial approach focused on psychological well-being and work-life harmonization to reduce burnout rates